Tax Structure Implications on Exchange Rate and Infrastructural Development in Nigeria - Ambaiowei Tari Ebiowei; Asian Asian Umobong (Training & Research Institute - Jeramba Ilmu Sukses, 2023)
The study examined the relationship between tax structure and exchange rate, and capital expenditure using secondary data obtained from Central bank of Nigeria and Federal inland revenue annual bulletin for the period 1994 to 2022 using multiple regression and auto regressive distributive lag. Tax structure was divided into direct and indirect tax consisting of PPT, CIT and VAT while the dependent variable was proxied by exchange rate and capital expenditure. Unit root test for stationarity was conducted using Augmented Dickey Fuller and Kwiatkowski Phillips Schmidt Findings show that in the short run the coefficients of the tax structure variables passed the significance test at the 5 percent level indicating that tax revenues critically influence short run changes in capital expenditure. The coefficients of current PPT, current CIT and complete VAT are all positive, which show that all forms of taxes promote capital spending by government in Nigeria in the short run. Thus, increasing tax revenues will immediately deliver positive impacts on the budgetary provisions for capital spending in Nigeria. The study also found that capital expenditure improves exchange rate, the positive impact of tax revenues on short run capital expenditure confirms that taxes have significant indirect impact on short run macroeconomic performance in Nigeria. The long run results also report interesting outcomes The coefficients of the two direct tax components are significant at the 5 percent level, while that of VAT failed the test at the 5 percent level. This result shows that while PPT and CIT significantly influence capital expenditures in Nigeria, VAT has no significant impact. It also suggests that VAT does not exert indirect long run effects on macroeconomic performance through the capital expenditure channel. The coefficient of CIT is however negative, indicating that increasing CIT tends to reduce capital expenditures in Nigeria. On the other hand, the coefficient of PPT is positive which indicates that only PPT tends to directly improve capital expenditure or indirect improve long run macroeconomic performance through the channel of capital expenditure in Nigeria. The coefficient of public debt failed the significance test in the long run estimates, while the coefficient of exchange rate is significant at the 5 percent level and also possesses a negative sign. This implies that in the long run, exchange rate depreciation tends to limit capital expenditures in Nigeria. In particular every one percent rise in CIT was found to be consistent with a 0.877 percent rise in VAT, while a percent rise in PPT is accompanied by an increase in CIT by 0.93 percentage point. The relationship was found to be strong in Nigeria and also suggests that tax revenue in Nigeria is linked. the study found that only direct taxes led to improvement in exchange rate in the long run. This implies that direct taxes may be more effective in maintaining macroeconomic stability in Nigeria than application of indirect taxes. increases in indirect taxes tend to produce external effects that do not fully guarantee improvements in macroeconomic in Nigeria. direct tax component only improves exchange rate. Indeed, it was found that CIT revenues essentially lead to reduction in capital expenditure in the long run in Nigeria. That both PPT and CIT have significant negative impacts on exchange rate in the long run in Nigeria, indicating only the direct component of the tax structure in Nigeria significantly enhances exchange rate performance in Nigeria over time, while the effect of indirect tax components is insignificant. That only PPT has a significant indirect or channeled impact on macroeconomic performance through the capital expenditure in Nigeria. We recommend that government should pursue policies and programs that would help ensure exchange rate stability and boost local production for both consumption and export. In addition, a holistic program of economic reforms is important to complement the exchange rate policy and stimulate economic growth